E-government interoperability and information resource integration frameworks for aligned development - Gottschalk, Petter 1950-; Solli-Sæther, Hans (Premier reference source, 2009)
"This book focuses on the integration of new technologies into digital government, generating new insights into e-government interoperability" - Provided by publisher